Agro-Food Dynamics in a Region's Growth - Anastasios Michailidis; Efstratios Loizou; Konstadinos Mattas; Aikaterini Melfou (European Regional Science Association (ERSA), 2006)
Regional development depends highly in the allocation of developing funds -through development policies- among the various sectors of regional economies. In order to safeguard the most efficient use of investments analytical tools visualizing the economy as a whole in the form of a general equilibrium should be adopted. In this paper the role of agro-food sectors and agriculture in regional economic growth is examined. Despite the diminishing contribution of agriculture and agro-food sectors in the formation of an economy's gross output and employment, their indirect influence upon the rest of the economy most of the times is not completely cast up. It is evidence that over the last two decades the share of agriculture in Greece's GDP is substantially dropped. This fact many times used as a guide to support decisions in directing regional developing funds far from agriculture. On the other side, food sector's share in processing industries is growing and its contribution and interrelation with other sectors has not been well assessed. Thus in the present paper, the indirect contribution of agro-food sectors in a region's economy is measured and compared to non-agricultural sectors. Linkage relationships and interdependencies between food and non-food sectors are sought and their role in strengthening the regions growth is contemplated. The identification of such relationships is very important, as the path to development in some regions is very sensitive to sectoral interdependencies. To accomplish the aforementioned objectives, an Input-Output framework was employed in a regional level (Thessalia, Greece). Utilizing an employment based Location Quotient (LQ), developed by Flegg et al (1995) -the FLQ- the national I-O table is regionalized for the Greek (NUTS 2) region. The regionalization procedure was performed by following the hybrid GRIT technique. Employing the regional I-O table, linkage coefficients, that identify the dynamics of key sectors, were estimated. In addition the regional output generated due to food sector and non-food sector activity traced out to compare the relative dynamics. Results clearly demonstrate that the nexus of food non-food sectors is determinant in regional growth plans and the particular interdependencies, in every particular region, must carefully considered.
Keywords: 330